African urbanims: Reinterpreting the marks of the church - Naudé, Piet (Stellenbosch Theological Journal, 2016)
This essay presents a broad analysis of African “cityness” and brings this analysis in relation to an ecumenical interpretation of the marks of the church. The aim is to construct an “urban ecclesiology” where the realities of African cities influence our understanding of the church, and where – in turn – the marks of the church provides some pointers to a life of community, justice and fulfilment in the city.